Impact of COVID-19 on Subjective Well-being and Community Im-portance-Performance in Sanitation Programs in Jakarta, Indonesia - Evi Siti Sofiyah; Betanti Ridhosari; Sapta Suhardono; Chun-Hung Lee; I Wayan Koko Suryawan (Forum Geografi)
This research investigates the critical impacts of the COVID-19 pandemic on subjective well-being and evaluates community responses to sanitation programs within three urban villages in Koja, Jakarta. Utilizing Importance-Performance Analysis (IPA), the study comprehensively assesses community perceptions and engagement levels with key sanitation aspects including access to defecation and treatment, treatment quality, aesthetic quality, monitoring practices, and socialization efforts in drainage and treatment. Advanced statistical models, such as probit and logit regressions, are employed to explore how demographic variables like housing stability, gender, and active involvement in community-based sanitation programs influence these perceptions and actions toward sanitation. The findings reveal significant disparities in satisfaction levels with existing sanitation services, pinpointing areas such as monitoring and treatment services that are critically underperforming and require immediate improvement. This study highlights the urgency of addressing these issues in the face of the ongoing pandemic, reflecting on the novel insights into the complex dynamics between demographic factors and the effectiveness of sanitation programs. Our approach aims to elevate the standard of sanitation services to enhance the resilience and well-being of urban communities against the multifaceted impacts of COVID-19. These strategic improvements are vital for sustaining public health and promoting a safer, healthier living environment in densely populated urban areas, where effective sanitation is crucial for mitigating health risks and enhancing public safety.